Discrimination of p53 immunohistochemistry‐positive tumors by its staining pattern in gastric cancer. (30th October 2014) - Ando, Koji; Oki, Eiji; Saeki, Hiroshi; Yan, Zhao; Tsuda, Yasuo; Hidaka, Gen; Kasagi, Yuta; Otsu, Hajime; Kawano, Hiroyuki; Kitao, Hiroyuki; Morita, Masaru; Maehara, Yoshihiko
Abstract Immunohistochemistry staining of p53 is a cheap and simple method to detect aberrant function of p53. However, there are some discrepancies between the result of immunohistochemistry staining and mutation analysis. This study attempted to find a new definition of p53 staining by its staining pattern. Immunohistochemistry staining of p53 and TP53 gene mutation analysis were performed in 148 gastric cancer patients. Also SNP‐CGH array analysis was conducted to four cases. Positive staining of p53 was observed in 88 (59.5%) tumors. Tumors with positive p53 staining showed malignant features compared to negative tumors. Mutation of TP53 gene was observed in 29 (19.6%) tumors with higher age and differentiated type. In positive p53 tumors, two types could be distinguished; aberrant type and scattered type. With comparison to TP53 gene mutation analysis, all the scattered type had wild‐type TP53 gene (P = 0.0003). SNP‐CGH array showed that scattered‐type tumors had no change in the structure of chromosome 17. P53‐scattered‐type staining tumors may reflect a functionally active nonmutated TP53 gene. In interpretation of p53 immunohistochemistry staining, distinguishing p53‐positive tumors by their staining pattern may be important in gastric cancer.